ChemInform Abstract: DIFLUORPHOS and SYNPHOS in Asymmetric Catalysis: Synthetic Applications. Issue 33 (19th August 2014) - Prevost, Sebastien; Ayad, Tahar; Genet, Jean‐Pierre; Phansavath, Phannarath; Ratovelomanana‐Vidal, Virginie
Abstract Review: 58 refs.